Fractal analysis of Jackson Pollock's painting evolution. (February 2016) - Alvarez-Ramirez, J.; Ibarra-Valdez, C.; Rodriguez, E.
Highlights: The evolution of the fractality indices of Pollock's paintings was studied. One transition involves a change in the correlations dimension by 1937. A second transition implicates a shift in the short-scale Hurst exponent by 1945-1946. The first change was influenced by Mexican muralist Siqueiros. The second change was motivated by the natural landscapes at Springs, Long Island. Abstract: By mid-1940s, Jackson Pollock, one of the most influential artists in the twentieth century plastic art, developed a unique painting technique (pouring and dripping) to generate complex non-figurative patterns. It has been argued that methods from fractality theory are suitable for characterizing these complex patterns. In fact, recent studies have shown that, indeed, Pollock's drip paintings are fractal, multifractal, multiscaling and evolved to higher complexity from 1945 to 1950. However, the development of this drip and pouring technique was neither instantaneous nor spontaneous, but influenced by diverse cultural and personal factors along of Pollock's life. The aim of this work is to study the evolution of some fractality indices of Pollock's paintings for the period from 1930 to 1955 and, in this form, detect changes in this painting technique and relate them to major cultural influences. To this end, about 30 paintings are analyzed by applying a two-dimensional detrended fluctuation analysis (DFA). Results indicate two large shifts in the fractality indices. One transition involves a change in the correlations dimension by 1937, while a second transition implicates a shift in the short-scale Hurst exponent by 1945-1946. Based on descriptions from Pollock's biographers, it is postulated that the first change may be strongly influenced by Mexican muralist Siqueiros and the second one by the moving of Jackson Pollock and Lee Krasner for living in the natural landscapes at Springs, Long Island. Our findings in this work support these claims.